Cloud-based solutions to the levelling education in physics in the context of Latvian education - Juskaite, Loreta (International Journal of Engineering and Technology, 2018)
With the rapid development of new technologies, the priority directions and goals of education are also changing. As the intensity of life is constantly growing, it requires new solutions. There is a high demand for not only different teaching materials, but also for a different organization of the learning process, a different educational policy, as well as the opportunity to quickly and continuously introduce new solutions. In 2017, â€œi-Zvaigzne.lvâ€ publishing company presented a new cloud-based solution [1] "Online Tests in Physics for Grade 12" and [2] "Physics:Â High School course!" These are extensive electronic collections of online learning tasks, tests, tasks solution examples and tasks for self-testing in the Latvian language. The aim of the research - to theoretically analyse and empirically justify the use of cloud services in the context of levelling education.Â Â